2002
DOI: 10.1016/s0167-4889(02)00201-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rho/Rho-kinase signaling downregulates plasminogen activator inhibitor-1 synthesis in cultured human monocytes

Abstract: Increased production of plasminogen activator inhibitor-1 (PAI-1) in plaques plays a role in the pathogenesis of atherosclerosis. This study was conducted to investigate the effect of blockade of Rho/Rho-kinase signaling on the synthesis of PAI-1 in cultured human peripheral blood monocytes. HMG-CoA reductase inhibitors (statins) and inhibitors of Rho and Rho-kinase were added to monocyte cultures. The levels of PAI antigen and mRNA were determined by Western blotting and RT-PCR, respectively, and PAI-1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
3
19
1
2
Order By: Relevance
“…1C) and PBMC (Fig. 1D), clearly contradicts earlier observations of reduced Rho activation in myeloid (19) and lymphoma cells (20), as determined by similar GTP-binding assays. Because the latter reports applied longer incubations (at least 48 h) with HMGCRI, we next performed a kinetic with atorvastatin in PBMC.…”
Section: Increased Rho Gtp Loading In T Cells Following Ggpp Depletionsupporting
confidence: 76%
“…1C) and PBMC (Fig. 1D), clearly contradicts earlier observations of reduced Rho activation in myeloid (19) and lymphoma cells (20), as determined by similar GTP-binding assays. Because the latter reports applied longer incubations (at least 48 h) with HMGCRI, we next performed a kinetic with atorvastatin in PBMC.…”
Section: Increased Rho Gtp Loading In T Cells Following Ggpp Depletionsupporting
confidence: 76%
“…We also showed that both hydrophilic and lipophilic statins suppress molecular expression, including tissue factor and plasminogen activator inhibitor-1, by depletion of cellular geranylgeranylpyrophosphate (GGPP) 16,[26][27][28] . Taken together with other reports [29][30][31] , our previous study clearly demonstrated the exact mechanism of the pleiotropic effect that statins rapidly blocks the activation of unprocessed GDP-RhoA by inhibiting geranylgeranylation 9) .…”
Section: Discussionmentioning
confidence: 95%
“…For example, statins increase endothelial nitric oxide synthase expression, 14 decrease smooth muscle cell proliferation, 15 reduce matrix metalloproteinase activity and tissue factor production by macrophages, 16,17 increase fibrinolytic activity, 18 and have immunomodulatory and antiinflammatory actions such as increasing resistance to complement 19 and decreasing dendritic cell maturation. 20 Many of these effects are reversed only with geranylgeranyl pyrophosphate and not with farnesyl pyrophosphate, suggesting that inhibition of Rho isoprenylation by statins is the predominant mechanism by which statins exert their antiatherogenic activities.…”
Section: Discussionmentioning
confidence: 99%
“…12 Extending our data to the clinical situation, the differential response of the volunteers suggests that individual patients will benefit to different degrees from the pleiotropic effects of statins, independently of the lipid-lowering effect. The increase in nonisoprenylated inactive form of RhoA in PBMCs has been linked to the atheroprotective effects of statins on these cells, such as downregulation of plasminogen activator inhibitor-1 synthesis, 18 decreased transcription of matrix metalloproteinases and adhesion molecules in monocytes, 16 decreased monocyte-endothelial cell interactions, 23 and inhibition of activation and proliferation of T lymphocytes. 24 The most responsive patients will be expected to benefit from lipidlowering and from pleiotropic atheroprotective effect of statins.…”
Section: Discussionmentioning
confidence: 99%